Determination of the Health Costs of Effective Detoxification Based on Effective Doses of Benzene Exposure To workers in oil and gas mining companies, Central Java, Indonesia - Ayu Prima Kartika1, Vivi Budiarti1, Achmat Kuncoro1, Charles Kimura1, Abdul Rohim Tualeka2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Benzene is a natural component of crude oil and gasoline. Benzene occurs naturally in crude oil at levels of up to 4 g / l and benzene has been classified as a group carcinogen. This research was conducted in oil and gas mining companies, West Java, Indonesia. This research was conducted using a cross sectional method. The sample in this study were 30 respondents. The variables that became the data of this study included benzene concentration (C) daily exposure time (tE), frequency of annual exposure (fE), duration of exposure (Dt), height, weight, age, respiration rate (BR), and urine of workers. The results showed an average measurement of benzene concentration in oil and gas mining companies, West Java, Indonesia on the KPC portion of 0.1 ppm and in the laboratory section at 0.2 ppm, which means it is still below the Threshold Value (NAB) which is equal to 0.5 ppm5. Obtained the highest effective dose to be consumed by respondents in the KPC unit for beef liver is 6x10-4 kg at a cost of IDR 33,31046813, chicken 3x10-4 kg at a cost of IDR 13,1251,9985, and avocado is 4x10-6 kg at a cost of IDR 0,16206628 , while the highest effective dose to be consumed by respondents in the laboratory unit for beef liver is 1x10-2 kg at a cost of IDR 12,14687477, chicken 6x10-4 kg at a cost of IDR 22,14504841, and avocado is 6x10-6 kg at a cost of IDR 0, 27344083. Control recommendations are to adopt a lifestyle that can minimize exposure to poisons and improve detoxification pathways.